2022
DOI: 10.3389/fpsyg.2022.918834
|View full text |Cite
|
Sign up to set email alerts
|

Is the Association Between Early Childhood Screen Media Use and Effortful Control Bidirectional? A Prospective Study During the COVID-19 Pandemic

Abstract: Individual differences in effortful control, a component of temperament, reflecting the ability to use attention and other cognitive processes to self-regulate emotion and behavior, contribute to child academic adjustment, social competence, and wellbeing. Research has linked excessive screen time in early childhood to reduced self-regulation ability. Furthermore, research suggests that parents are more likely to use screens with children who have more challenging temperaments, such as low levels of effortful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 79 publications
1
17
0
1
Order By: Relevance
“…However, the association between screen media and a child's temperament is likely to be bidirectional. While parents are likely to expose more difficult infants and toddlers to more screen time to regulate children's behavior (Radesky et al., 2016), excessive screen time has also negative effects on a child's emotional regulation (Fitzpatrick et al., 2022, 2023). For example, Fitzpatrick et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the association between screen media and a child's temperament is likely to be bidirectional. While parents are likely to expose more difficult infants and toddlers to more screen time to regulate children's behavior (Radesky et al., 2016), excessive screen time has also negative effects on a child's emotional regulation (Fitzpatrick et al., 2022, 2023). For example, Fitzpatrick et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fitzpatrick et al. (2022, 2023) who studied preschoolers' screen use during the COVID‐19 pandemic found that children's screen time at age 3.5 years predicted increased proneness to anger/frustration and decreased effortful control at age 4.5 years. Another possible explanation for our findings is that the association between screen time and a child's temperament is explained by other sociocultural factors, such as rules around screen time, parenting style, and parenting stress (Leppänen et al., 2020; Shin et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schon lange ist bekannt, dass die vor dem Bildschirm verbrachte Zeit sich negativ auf die kindliche Entwicklung auswirkt, wobei sowohl die kognitive als auch die psychosoziale Entwicklung betroffen ist. Neuere Längsschnittuntersuchungen gehen über Korrelationen hinaus und weisen deutlich auf einen kausalen Zusammenhang hin 15 , 39 . So beeinflusst die Bildschirmzeit im Vorschulalter von 2 bzw.…”
Section: Umweltfaktorenunclassified